Efeito da administração oral de aflatoxina B1 nas convulsões induzidas em ratos - Trombetta, Francielle (2014)
Aflatoxins are produced by Aspergillus flavus fungi, mainly A. parasiticus and A. nomius. Aflatoxin B1 (AFB1) is the most common and highly toxic mycotoxin, presents carcinogenic, mutagenic and teratogenic effects. This mycotoxin has been detected in cultures of worldwide importance such as maize, groundnuts, beans, rice, wheat, cotton, sorghum, fruit and also in animal feed. AFB1 exerts its effects after its conversion into liver 8,9-epoxide by the action of cytochrome P-450, which reacts with cellular macromolecules, including proteins, RNA and DNA. Furthermore, there is an increase in levels of reactive oxygen species, altered neurobehavioral performance, damage to motor coordination, and decreased protein levels. Studies show that AFB1 alter the levels of neurotransmitters such as norepinephrine, serotonin and dopamine, and it is known that these changes influence the behavior of animals, also inhibits the activity of the enzyme Na+, K+-ATPase. This enzyme in the brain is essential for the maintenance of the electrochemical gradient, maintenance of resting potential and the release and uptake of neurotransmitters. Thus, a decrease in activity Na+, K+-ATPase could cause increased neuronal excitability, facilitating the occurrence of seizures. Thus, the aim of this study was to investigate the influence of AFB1 in facilitating seizures induced by a subconvulsant dose of pentylenetetrazol (PTZ), and evaluate its toxic effects on the brain, by determining the activity of Na+, K+-ATPase and oxidative stress parameters after acute exposure to AFB1 in rats. EEG recording of the animals was performed after acute oral administration of AFB1 (250 mg/kg) followed by a subconvulsant dose of pentylenetetrazol (30 mg/kg, ip). Prior administration of AFB1 to PTZ reduced the latency of myoclonus, did not alter the total amplitude of the brain waves, and concomitant exposure to PTZ reduced the activity total, α1 and α2/α3 of the enzyme Na+, K+-ATPase in the cerebral cortex. In the hippocampus, the AFB1 and PTZ reduced total and α2/α3 activity of the Na+, K+-ATPase. The AFB1 not alter the activity of catalase (CAT), and glutathione-S-transferase (GST) in the cerebral cortex of animals. We conclude that AFB1 exerts neurotoxic effect, facilitating seizures induced by PTZ possibly by inhibiting Na+, K+-ATPase activity.